Effects of local administration of hydrocortisone on cartilage degradation in vivo. Issue 3 (June 1984) - Sedgwick, A D; Sin, Y M; Moore, A R; Edwards, J C; Willoughby, D A
Abstract : The effect of corticosteroid on autologous minced cartilage transplanted into facsimile synovial cavities has been studied. The soluble form of hydrocortisone, as the sodium succinate, reduced proteoglycan loss from cartilage in a dose-dependent manner. In contrast, insoluble hydrocortisone acetate, if given directly into the cartilage-containing cavity, enhanced proteoglycan loss. Injection of the same dose of drug into the inflamed lining tissue reversed this effect. These findings suggest that intra-articular steroid injection may enhance cartilage damage if insoluble preparations are used, but that this may be overcome by injecting into the inflamed lining tissue rather than into the cavity itself.